MiR-135a and MRP1 play pivotal roles in the selective lethality of phenethyl isothiocyanate to malignant glioma cells - Zhang, Taolan (Am J Cancer Res, 2016)
Amounting evidence has demonstrated that phenethyl isothiocyanate (PEITC) is a strong inducer of reactive oxygen species (ROS) and functions as a selective killer to various human cancer cells. However, it remains obscure whether PEITC has potential selective lethality to malignant glioma cells. Thus in this study, we performed multiple analysis such as MTT assay, Hoechst 33258 staining, flow cytometry, foci formation, RT-PCR, Western blot, and transfection to explore the selective lethality of PEITC to malignant glioma cells and the underlying mechanisms. We found that PEITC induced a selective apoptosis and suppressed tumorigenicity and migration of malignant glioma cells. Furthermore, we found PEITC significantly induced GSH depletion, ROS production, caspase-9 and caspase-3 activation, and miR-135a upregulation in malignant glioma cells but not in normal cells. Moreover, PEITC activated the miR-135a-mitochondria dependent apoptosis pathway as demonstrated by downregulation of STAT6, SMAD5 and Bcl-xl while upregulation of Bax expression and Cytochrome-C release in malignant glioma cell lines but not in the immortalized human normal glial HEB cells. Correspondingly, the above PEITC-induced activation of the ROS-MiR-135a-Mitochondria dependent apoptosis pathways in malignant glioma was attenuated by pre-transfection with miR-135a inhibitor, pre-treatment with multidrug resistance-associated protein 1 (MRP1) inhibitor Sch B, or combination with glutathione (GSH). These results revealed that PEITC selectively induced apoptosis of malignant glioma cells through MRP1-mediated export of GSH to activate ROS-MiR-135a-Mitochondria dependent apoptosis pathway, suggesting a potential application of PEITC for treating glioma.